The Whole Is Not Always the Sum of the Parts: Synergistic Plant Responses to Combined Environmental Stresses - Amorim-Silva, Vitor; Botella-Mesa, Miguel Ángel (Wiley, 2025)
Numerous studies examining plant-environment stress interactions cultivate plants under optimal, non-stressful conditions before introducing individual stress factors to analyse response mechanisms, which clearly is an oversimplification. In nature, plants thrive under suboptimal conditions, encountering multiple environmental cues such as day-night temperature variation, abiotic stressors, soil heterogeneity, pathogens, herbivores and so forth.
Keywords: Plantas - Efectos del estrés; Flavonoides; Spodoptera frugiperda resistence; Plant-environment stress interactions; Flooding; Flavonoid biosynthesis; Salicylic acid